Pengaruh Persepsi Dukungan Organisasi dan Efikasi Diri Terhadap Employee Engagement pada PT. United Tractors Tbk Pekanbaru - Shafina Aurely Nurhayati; Suryalena Suryalena (Jurnal Simki Economic, 2023)
The aim of this research is to find out the simultaneous and partial effect of perceived organizational support and self-efficacy on employee engagement at PT. United Tractors Tbk Pekanbaru. This study uses a quantitative methodology. Questionnaires were distributed as part of the data collection procedure. The total sampling technique was used for a sample of 57 respondents, and SPSS was used to process the results. Methods of analysis include reliability, validity, and heteroscedasticity tests, multicollinearity, normality, coefficient of determination, multiple linear regression analysis, and hypothesis testing, namely the t test and F test. The result of this study is that employee engagement is significantly influenced by perceptions of organizational support. The second shows that self-efficacy significantly influences employee engagement.